Fruit Microtakaful Scheme Working Framework in Malaysia - Salleh, Fauzilah; Bakar, Nor Mazlina Abu; Ismail, Nur Salina; Rashid, Norfadzilah; Deraman, Wan Jemizan Wan (Indonesian Journal of Sustainability Accounting and Management, 2023)
Microtakaful is an emerging concept in the insurance industry that aims to provide low-cost, accessible, and Sharia-compliant insurance products to the underserved populations. In Malaysia, the Fruit Microtakaful Scheme has been introduced to address to the needs of low-income households, particularly those in rural areas. There is no gainsaying that microtakaful plays a pivotal role in protecting the lives of low-income farmers as it helps reduce potential risks, they are exposed to curb unforeseen calamities, but there is still low coverage for low-income farmers. Consequently, providing microtakaful for low-income farmers is highly necessary. This article presents a working framework of the Fruit Microtakaful Scheme in Malaysia, including its operational model, distribution channels, marketing strategy, and risk management approach. This study explored the Fruit Microtakaful Scheme framework for Malaysia’s smallholder farmers. A focus group discussion that involved ten participants from various agencies related to the Takaful industry was conducted to determine the underlying basis of the FMTS framework, with the Central Bank of Malaysia as the regulator. The discussion revealed the need for protection against floods, droughts, pests, diseases, season contributions, and the implementation of FMTS. The fruit microtakaful framework for smallholder farmers in Malaysia was presented in this study